What does European institutional integration tell us about trade integration? - Melanie Leiner-Killinger; Christophe Madaschi; Melanie Ward-Warmedinger (European Central Bank (ECB), 2005)
This paper analyses trends in working time inthe euro area, in comparison with the US, over the period 1970 to 2004 and examines the causes and consequences of the observed changes. Between 1970 and 2004, a downward trend in average annual hours worked per worker can be observed for the euro area as a whole, all individual euro area countries and the United States. In contrast to the US, the euro area and a number of euro area countries also experienced a significant decline in annual hours worked per capita (“labour utilisation”) over the last three decades. Data reveal important disparities across countries –both in trends and levels. While some countries managed to reverse their downward trends inlabour utilisation in the 1980s and 1990s, the level of average hours worked per capita in 2004 remained significantly below their 1970 levels for all euro area countries for which data are available. From a policy perspective, falling annual average hours worked per worker or per capita are not a problem per se, ifthey reflect preferences. For example,increasing shares of voluntary part-time employment across many euro area countries, whilst increasing European employment rates, have contributed to the downward trend in average annual hours per worker. However, to the extent that low working hours are due to institutional features which create disincentives to work, such as high tax wedges and high unemployment benefits, or enforced reductions in working hours, these factors should be addressed.
Keywords: J3; J22; J24; E24; D02; 330; Annual hours of work; workingtime; labour utilisation; productivity; percapita income; institutions; working timelegislation; Europe and US; part-time work; preferences; labour costs; employment.; Arbeitszeit; Eurozone; EU-Staaten